A comparative study on the efficacy of drotaverine and valethamate on cervical dilatation during labour: a prospective study from a tertiary care hospital of Rajasthan - Khatri, Mitali; Joshi, Narendra; Saraswat, Chetan Prakash; Shrivastava, Vanshika; Choudhary, Neeraj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2026)
Background: Numerous drugs have been used to shorten the active phase of labour. how rationale is to use these drugs to shorten the active phase of labour? do they really shorten the duration of labour? What adverse effects do they have on the baby and the mother? These questions were the basis to perform the present study of comparing two of such drugs, injection drotaverine and injection valethamate bromide in primi and multigravidas. Methods: A randomised control trial was conducted to compare the efficacy of drotaverine and valethamate on cervical dilatation during labour among 140 cases (70 cases each) in Department of Obstetrics and Gynaecology, RNT Medical College, Udaipur (Rajasthan). Results. The mean duration of first stage of labor was 190.87±38.7 minutes in the Drotin group, 257±44.54 minutes in the epidosin group and 286.68±103.1 minutes in the control group. These differences were statistically significant. There was no significant difference in the duration of second and of third stage. Conclusion: Baseline cervical dilatation and effacement were comparable in both the groups. The rate of cervical dilatation was significantly faster among drotin group than valethamate. Mean injection to delivery interval was also significantly shorter in valethamate group compared to Drotin group.